A pilot primary school active break program (ACTI-BREAK): Effects on academic and physical activity outcomes for students in Years 3 and 4. Issue 4 (April 2019) - Watson, Amanda J.L.; Timperio, Anna; Brown, Helen; Hesketh, Kylie D.
Abstract: Objectives: To assess the feasibility and efficacy of a 6-week pilot active break program (ACTI-BREAK) on academic achievement, classroom behaviour and physical activity. Design: Pilot cluster randomised controlled trial. Methods: 374 children in Year 3 and 4 (74% response) were recruited from six schools across Melbourne, Australia. Schools were randomised to the ACTI-BREAK intervention or usual teaching practice. The intervention involved teachers incorporating 3 × 5 min active breaks into their classroom routine daily. Academic achievement was assessed using 1-min tests in reading and mathematics; classroom behaviour at the individual and whole class level was observed by teachers; and physical activity levels were assessed using accelerometers. Multilevel mixed effects linear regression models were conducted using intention to treat (ITT) and per protocol (PP) analyses. Results: Significant intervention effects were found for classroom behaviour at the individual level (ITT B = 16.17; 95% CI: 6.58, 25.76); effects were stronger for boys (B = 21.42; 95% CI: 10.34, 32.49) than girls (B = 12.23; 95% CI: 1.52, 22.92). No effect was found for classroom behaviour at the whole class level, reading, math or physical activity. PP findings were similar. Conclusions: Implementing active breaks during class time may improve classroom behaviour, particularly for boys. There was no evidence to suggest that implementing active breaks had any adverse effect on academic achievement or classroom behaviour, which may encourage classroom teachers to incorporate active breaks into their routine.